“Taking Risks” with Literacy Acoustics - Bryan Ripley Crandall; Tanya Baker; Nicole Brown; Donna Delbasso; Kwame Alexander; Attallah Sheppard (Study and Scrutiny)
This article is a May 28, 2015, National Writing Project (NWP) interview with Newbery Award-winning author Kwame Alexander about contributions made to yearlong professional development collaboration between K-8 teachers at Hill Central in New Haven, Connecticut, and Connecticut Writing Project at Fairfield University. The interview, A Talk with Kwame Alexander, which aired on BlogTalkRadio ,is now available in its entirety via Apple Podcasts.